Human security and empowerment in Asia beyond the pandemic - Anthony, Mely Caballero; Mine, Yōichi 1961-; Ishikawa, Sachiko 1958- (Politics in Asia, 2024)
Against the backdrop of global COVID-19 pandemic setbacks, this edited volume is a timely contribution to revisit the comprehensive framing of human security and development by examining the protection-empowerment nexus applied to different vulnerable groups and populations affected by the pandemic. While much of today's human security literature focuses on the concept of protection from states, this book provides new perspectives on the human security concept by exploring empowerment from theoretical and practical perspectives. It also encourages readers to reconsider the agency of vulnerable populations in dealing with the challenges posed by the pandemic. Examining eight case studies from Southeast Asia and Japan, the contributors to this book concentrate on demonstrating the importance of empowerment in enriching our understanding of human security. They focus on vulnerable groups' and communities' responses to diverse threats to their lives, livelihoods and dignity. These cases include key human security concerns, such as an ageing society, poverty, environment, food security, forced migration, gender, health, peace and justice - all compounded and exacerbated by the COVID-19 pandemic. An essential resource for students and scholars of human security in the aftermath of COVID-19 and its wider impacts. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license"--